Effects of value and interest intervention on EFL student teachers’ research motivation in the Chinese context - Bi, Peng; Liu, Honggang (Frontiers in Psychology, 2022)
Language teacher research is conducive to the development of teachers’ teaching skills and professional careers. Thus, many English teacher education programs require student teachers to do research. However, some empirical findings suggest that English as a foreign language (EFL) student teachers lack research motivation. Consequently, finding suitable interventions to increase their research motivation has become increasingly necessary. In light of the importance of research motivation intervention, this study involved designing an experiment to identify the effect of a value and interest intervention including the sharing of positive research experiences to improve student teachers’ research motivation. Quantitative questionnaires and qualitative semi-structured interviews were used to gather evidence on the change in student teachers’ research motivation during the intervention. The interview data revealed that student teachers’ research motivation was influenced by their belief in the value of research to their teaching practice. The experiment results suggested that student teachers’ intrinsic and extrinsic research motivations both increased after the intervention. However, the intervention was not effective in curbing their failure avoidance tendency. Pedagogical implications of the results are discussed at the end of this article.